AI COMPANIONS AND LONELINESS IN UNIVERSITY STUDENTS: A PRE-POST EXPERIMENTAL STUDY (Contemporary Journal of Social Science Review, 2026)
Loneliness has emerged as a pressing mental health concern, exacerbated by digitalization and reduced face-to-face social interactions. With the rise of artificial intelligence (AI), particularly chatbots designed for emotional and conversational engagement, this study investigates whether AI companions can mitigate loneliness and potentially serve as substitutes for new human connections. Grounded in Social Presence Theory, Attachment Theory, and the Media Equation Theory, a pre-post within-group experimental research design was employed involving 5 university students aged 20–24 from Okara University. The UCLA Loneliness Scale (Version 3) was used to measure participants’ loneliness before and after interaction with the AI companion. Results indicated a reduction in loneliness scores after interacting with the AI companion, suggesting that AI companions may provide meaningful emotional support, though they are not complete substitutes for human interaction. The study provides insights for mental health professionals, educators, and AI developers aiming to integrate digital companions into support systems.